2011
DOI: 10.1128/jvi.01592-10
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibody-Resistant Hepatitis C Virus Cell-to-Cell Transmission

Abstract: Hepatitis C virus (HCV) can initiate infection by cell-free particle and cell-cell contact-dependent transmission. In this study we use a novel infectious coculture system to examine these alternative modes of infection. Cell-to-cell transmission is relatively resistant to anti-HCV glycoprotein monoclonal antibodies and polyclonal immunoglobulin isolated from infected individuals, providing an effective strategy for escaping host humoral immune responses. Chimeric viruses expressing the structural proteins rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
259
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(275 citation statements)
references
References 51 publications
12
259
3
1
Order By: Relevance
“…32 To investigate whether apoE association is relevant in cell-to-cell transmission, we used an anti-apoE antibody (1D7) that binds the low-density lipoprotein receptorÀbinding domain of apoE 16 and inhibits HCV infection ( Figure 7A). Jc1 demonstrated an approximately 3-fold higher capacity to spread by direct cell-to-cell transmission than VL:JFH1 in this assay ( Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…32 To investigate whether apoE association is relevant in cell-to-cell transmission, we used an anti-apoE antibody (1D7) that binds the low-density lipoprotein receptorÀbinding domain of apoE 16 and inhibits HCV infection ( Figure 7A). Jc1 demonstrated an approximately 3-fold higher capacity to spread by direct cell-to-cell transmission than VL:JFH1 in this assay ( Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Whether the mechanisms of cell entry during cell-to-cell spread are distinct from those during cell entry by an extracellular virion is unclear. Most notably, there is conflicting data on whether cell-to-cell spread is CD81 independent (22,38,41) or not (7). OCLN knockdown has been reported to reduce cell-to-cell transmission by 2-to 3-fold in an assay in which spread, despite the presence of neutralizing antibodies in the supernatant, was defined as occurring cell to cell (7).…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, there is conflicting data on whether cell-to-cell spread is CD81 independent (22,38,41) or not (7). OCLN knockdown has been reported to reduce cell-to-cell transmission by 2-to 3-fold in an assay in which spread, despite the presence of neutralizing antibodies in the supernatant, was defined as occurring cell to cell (7). We used an agarose overlay to prevent cell-free spread and a HCV-NS3/4A-sensitive fluorescent reporter to monitor spread of infection in living cells and found that the absence of OCLN in target cells abolished cell-to-cell spread, indicating that this route is strictly OCLN dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Infected events in the second populations are considered as indicator of cell-to-cell transmission if the cell-free infectivity is blocked. This last condition can be 13 achieved by using saturating concentrations of neutralizing antibodies [171,186,187], particular virus mutants or target cells [101], or by culturing the cells under an agarose overlay that prevents Brownian motion of cell-free viruses [102,171]. The dual cell-based reporter system developed by Jones et al…”
Section: Cell-to-cell Transmissionmentioning
confidence: 99%